Thermal and mechanical properties of thiol-ene photocured thermosets containing DOPO-based liquid reactive flame retardant synthesized by metal-free azide-alkyne click reaction - ÇAKMAKÇI, EMRAH (My University, 2022)
The use of metal-free click reactions for the design and synthesis of novel flame retardant reactive monomers for thiol-ene photopolymerization is an intriguing area of research. In this study, we have prepared a new, 9,10-dihy-dro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO)-based, P-and N-containing reactive flame retardant via the metal-free azide-alkyne click reaction. For this purpose, first, azide-functionalized DOPO (DOPO-N-3) has been synthesized via Atherton-Todd reaction, and then this compound has been reacted with acetylene dicar-boxylic acid diallyl ester (ACDAE) to give the flame retardant monomer, namely DOPO-triazole diallyl ester (DTDAE). As prepared flame retardant monomer was characterized by nuclear magnetic resonance (NMR) and Fourier-transform infrared spectroscopy (FTIR) spectroscopies. Thermoset materials prepared by using DTDAE displayed over 90% gel content values. Polar triazole and phosphorous units rendered the surface of the ther-mosets hydrophilic. The thermal stability of the networks was enhanced, char yields increased and the glass transition temperatures (T(g)s) were increased. The limiting oxygen index (LOI) values of the crosslinked materials increased up to 27.8% as the DTDAE content was increased in the formulations. The synthetic method described in this study provides a practical approach for the synthesis of a P-and N-containing flame retardant through a metal-free azide-alkyne click reaction Also, the fact that DTDAE is in a liquid state makes this study valuable as it indicates that it can be easily dispersed. It is also believed this promising compound can be used in different polymer structures and formulations to develop new flame retardants in future studies to be applied in industrial applications.
Keywords: Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MALZEME BİLİMİ, KAPLAMALAR VE FİLMLER; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); MATERIALS SCIENCE, COATINGS & FILMS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Kimya (çeşitli); Genel Malzeme Bilimi; Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Chemistry (miscellaneous); General Materials Science; General Chemistry; Process Chemistry and Technology; Physical Sciences; Thiol-ene photopolymerization; Metal-free click reaction; Flame retardant; DOPO; Synergism; Thiol-ene photopolymerization; Metal-free click reaction; Flame retardant; DOPO; Synergism